Linguistic Crossroads: How do Indonesian Mother Tongues Shape English Language Acquisition? - Yazidi, Rachid EL; Amrizal (Educalingua Journal, 2025)
The influence of the mother tongue on second language acquisition has been widely studied, yet its specific impact on Indonesian learners of English remains underexplored. Grounded in the theoretical framework of language transfer and contrastive analysis, this study examines how the Indonesian language affects English pronunciation, grammar, and vocabulary acquisition. The research employed a qualitative approach, analyzing the linguistic patterns of Indonesian EFL learners through phonological, syntactic, and lexical perspectives. Findings indicate that phonological interference leads to sound substitution and syllable epenthesis, while syntactic transfer results in grammatical errors such as auxiliary omission and incorrect word order. Additionally, lexical interference causes misinterpretations due to false cognates and direct translations. These findings highlight the persistent influence of the mother tongue in shaping English proficiency. The study suggests that increasing exposure to authentic English input and employing explicit linguistic instruction can mitigate these challenges. Future research should explore intervention strategies and assess the long-term impact of language transfer. The study contributes to a deeper understanding of second language acquisition in multilingual contexts and offers pedagogical insights for EFL teachers in Indonesia.